Measurement and modeling of human T cell kinetics. - Macallan, D; Asquith, B; Irvine, A; Wallace, D; Worth, A; Ghattas, H; Zhang, Y; Griffin, G; Tough, D; Beverley, P (2003)
The ability to measure, describe and interpret T cell kinetics is pivotal in understanding normal lymphocyte homeostasis and diseases that affect T cell numbers. Following in vivo labeling of dividing cells with 6,6-D(2)-glucose in eight healthy volunteers, peripheral blood T cells were sorted by CD4, CD8 and CD45 phenotype. Enrichment of deuterium in DNA was measured by gas chromatography-mass spectrometry. A novel model of T cell kinetics, allowing for heterogeneity within T cell pools, was used to analyze data on acquisition and loss of label and calculate proliferation and disappearance rates for each subpopulation. Proliferation rates for CD45RO(+)CD8(+) cells and CD45RO(+)CD4(+) cells were 5.1% and 2.7% /day, respectively (equivalent doubling times: 14 and 26 days). CD45RA(+)CD8(+) lymphocytes and CD45RA(+)CD4(+) lymphocytes had slower proliferation rates, 0.5% and 0.6% / day, respectively (doubling time about 4 months). Disappearance rates of labeled cells were similar for all cell types (7%-12% / day) and exceeded corresponding proliferation rates. This disparity may be understood conceptually in terms of either phenotypic heterogeneity (rapid versus slow turnover pools), or history (recently divided cells are more likely to die). The new kinetic model fits the data closely and avoids the need to postulate a large external source of lymphocytes to maintain equilibrium.